2017
DOI: 10.1002/wsb.778
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic lure allows for capture of a high‐flying, endangered bat

Abstract: Mist nets are commonly used to capture free-flying bats; however, some bat species are very difficult to capture because of their flight behavior, habitat preferences, and ability to avoid nets. High-flying, open-space foragers are especially underrepresented by mist-net surveys. Few studies have investigated the effectiveness of using acoustic lures (playbacks of conspecific vocalizations) to increase capture success of bats in mist nets. We tested the efficacy of an acoustic lure to capture a high-flying rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
(49 reference statements)
1
21
0
Order By: Relevance
“…Acoustic surveys are routinely used to monitor bat activity patterns and changes in habitat use (Hayes et al , Parsons and Szewczak ). They are particularly effective for high‐flying species not easily captured in mist nets, such as Florida bonneted bats (Braun de Torrez et al ), which have distinct, identifiable echolocation calls (Belwood , Bailey et al ). Further, Florida bonneted bats have low frequency, high intensity calls that are much less sensitive to attenuation (from distance and vegetation) than higher frequency calls of other species (Parsons and Szewczak ), thus reducing site‐specific biases associated with vegetation structure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acoustic surveys are routinely used to monitor bat activity patterns and changes in habitat use (Hayes et al , Parsons and Szewczak ). They are particularly effective for high‐flying species not easily captured in mist nets, such as Florida bonneted bats (Braun de Torrez et al ), which have distinct, identifiable echolocation calls (Belwood , Bailey et al ). Further, Florida bonneted bats have low frequency, high intensity calls that are much less sensitive to attenuation (from distance and vegetation) than higher frequency calls of other species (Parsons and Szewczak ), thus reducing site‐specific biases associated with vegetation structure.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded all calls that overlapped with the range of f c for Brazilian free‐tailed bats ( Tadarida brasiliensis ; 18–33 kHz; Szewczak ), or that may have been low frequency social calls from non‐target bat species, acoustic echoes, insects, birds, or electronic noise. To aid in manual validation, we compiled a reference library of echolocation calls from hand‐released bats captured in mist nets and around known roost locations in south Florida (Braun de Torrez et al , ). We further examined all files identified as Florida bonneted bats to classify those containing feeding buzzes, reflective of foraging activity (Fenton , Coleman and Barclay ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, reducing branch cropping, and planting trees in tree gaps, may increase roost availability. Broadcasting conspecific feeding buzzes or social calls also may attract bats [60,81], but may not be equally effective across species. Due to the suspected adverse effects of chemical pesticides applied to trees where bats roost in foliage and the areas in which they forage [82,83], we recommend that some areas be left unsprayed for bats to have alternate foraging and roosting sites during such management events.…”
Section: Conclusion: Conservation and Management Implicationsmentioning
confidence: 99%
“…Acoustic lures have been used to increase capture rates for taxa such as birds (Sydeman et al 1998;Schaub et al 1999), and there is growing literature on their use for bats (Gillam 2007;Lintott et al 2014;Quackenbush et al 2016;Braun de Torrez et al 2017). Greenaway (2005, 2008) reported that even in areas where Bechstein's bat Myotis bechsteinii is known to occur in large numbers, individuals are rarely captured in nets.…”
Section: Introductionmentioning
confidence: 99%